2013
DOI: 10.1037/a0030697
|View full text |Cite
|
Sign up to set email alerts
|

Negative affective state mimics effects of perceptual load on spatial perception.

Abstract: Recent electrophysiological evidence showed that perceptual load and negative affective state can produce very similar early attention gating effects in early visual areas, modulating the processing of peripheral stimuli. Here we assessed the question whether these modulatory effects of perceptual load and negative affect (NA) lead to comparable changes in spatial perception abilities, which could be captured at the behavioral level. High perceptual load at fixation impaired the precise spatial localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Additional studies further strengthen the notion that modifications can occur for stimuli of varying complexity (e.g., primary visual analysis, size estimations, processing of social cues) and at early or later processing stages (e.g., Phelps et al, 2006; Bocanegra and Zeelenberg, 2009; Schmitz et al, 2009; Stefanucci et al, 2011; Rossi and Pourtois, 2013). When relatively “simple” target features were concerned, brief presentation of a fearful face as compared to a neutral one resulted in superior orientation sensitivity for images of low spatial frequency and attenuated orientation sensitivity for images of high spatial frequency (Bocanegra and Zeelenberg, 2009).…”
Section: Temporary Changes To Crossmodal Processing When Involving Afmentioning
confidence: 59%
See 1 more Smart Citation
“…Additional studies further strengthen the notion that modifications can occur for stimuli of varying complexity (e.g., primary visual analysis, size estimations, processing of social cues) and at early or later processing stages (e.g., Phelps et al, 2006; Bocanegra and Zeelenberg, 2009; Schmitz et al, 2009; Stefanucci et al, 2011; Rossi and Pourtois, 2013). When relatively “simple” target features were concerned, brief presentation of a fearful face as compared to a neutral one resulted in superior orientation sensitivity for images of low spatial frequency and attenuated orientation sensitivity for images of high spatial frequency (Bocanegra and Zeelenberg, 2009).…”
Section: Temporary Changes To Crossmodal Processing When Involving Afmentioning
confidence: 59%
“…Also, visual field processing is narrowed when in a negative mood and widened when in a positive mood (Schmitz et al, 2009; see also Gable and Harmon-Jones, 2010). In an ERP study, Rossi and Pourtois (2013) found that effective filtering (perceptual encoding) of peripheral task-irrelevant distractors was abolished when individuals were in a negative mood. Another study showed that height is overestimated when looking at high vs. low arousing pictures and that this effect is enhanced when individuals up-regulated their emotional experience (Stefanucci and Storbeck, 2009).…”
Section: Temporary Changes To Crossmodal Processing When Involving Afmentioning
confidence: 99%
“…), relaxation, anxiety, and avoidance, in the order just reported. Such scales are a reliable, simple, and rapid was to assess mood and anxiety state (Abend et al 2014; Cella and Perry 1986; Rossi and Pourtois 2013). Each question was followed by a 9-point Likert scale ranging from ‘not at all’ to ‘extremely’.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, these results suggest a representation of threat-related features already in early visual cortex, possibly mediating generalization of behavioral responses in new environments (Dunsmoor, Kragel, Martin, & LaBar, 2013). This in turn could be at the foundation of processes such as the generalization of fear (Dunsmoor, Prince, Murty, Kragel, & LaBar, 2011;Onat & Büchel, 2015), and could explain why anxiety maintenance can be sustained by attentional and perceptual biases also involving coarse visual mechanisms (Rossi & Pourtois, 2013).…”
Section: Role Of Stimulus Familiarity (See Figure 4 Panels B and C)mentioning
confidence: 99%